The Concept of Murtadha Muthahhari on Freedom and Equality of Women's Rights in Islam - Pasaribu, Sri Rahmadani (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
This article describes the concept of Murtadha Muthahari's thoughts on freedom and equality of women's rights in Islam. Studying freedom and equality of women's rights in Islam is essential to respond to misinterpretation of women, which causes Westerners to make wrong assumptions about women in Islam and issue negative ideas about Muslim women. The primary data of this article is Muthahhari's work entitled Women's Rights in Islam and Women's Philosophy in Islam. This study used an analytic description method with a factual historical approach regarding the characters. This article presents how Muthahhari explains emancipation, freedom, and equality of women's rights in Islam. Muthahhari explained that emancipation is a movement that determines the equality of women's rights against men's rights to obtain justice and happiness. Meanwhile, according to Muthahhari, the freedom and equality of women's rights in Islam is that women and men have equal rights but not freedom and equality, which is the same between equality and identity, must be distinguished. Different from other figures who study women's issues, Muthahhari uses methods from Islam by using philosophy and religion as a starting point.